1985
DOI: 10.1161/01.cir.71.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of left ventricular contraction to the generation of right ventricular systolic pressure in the human heart.

Abstract: To determine whether left ventricular (LV) contraction contributes to the generation of right ventricular (RV) systolic pressure in humans, LV and RV pressures and their first derivative (dP/ dt) were recorded simultaneously with micromanometer-tipped catheters in 11 conscious subjects. Seven subjects had normal LV and coronary angiograms. Four subjects had moderate LV dysfunction (resting ejection fraction 0.40 to 0.50), and three of these had coronary artery disease. During normal sinus rhythm, LV contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
1
4

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(66 citation statements)
references
References 52 publications
2
59
1
4
Order By: Relevance
“…In normal subjects, both LV effects on RV function [1][2][3]5,28 and RV effects on LV function 2,4,28 have been observed. These effects are important in functional single ventricles because there is no second ventricle to augment the function of the systemic ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In normal subjects, both LV effects on RV function [1][2][3]5,28 and RV effects on LV function 2,4,28 have been observed. These effects are important in functional single ventricles because there is no second ventricle to augment the function of the systemic ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6]28 The mechanism of free wall contribution is the fact that the myocardium is a "syncytium of muscle fibers tethered within a collagen network" 28 with muscle fibers in continuity between RV and LV. 29 Santamore et al 2 showed in rabbits that the free wall of one ventricle affects the contralateral ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Over the last 60 years, both experimental data and clinical experience show that a significant portion of the RV systolic pressure is a result of the left ventricle (LV) generating pressure that is transmitted through the interventricular septum (IVS). [3][4][5][6] This left to right ''ventricular assistance'' is influenced by RV volume and pressure and the transseptal pressure gradient. 7,8 The clinical impact of this interaction increases with increasing RV dysfunction.…”
Section: Résumémentioning
confidence: 99%